FDG Dose Extravasations in PET/CT: Frequency and Impact on SUV Measurements - Osman, Medhat M.; Muzaffar, Razi; Altinyay, Mustafa E.; Teymouri, Cyrus (Frontiers in Oncology, 2011)
Objectives: PET/CT with 18F-FDG has proven to be effective in detecting and assessing various types of cancers. However, due to cancer and/or its therapy, intravenous (IV) FDG injection may be problematic resulting in dose extravasations. In the most frequently used field of view (FOV), arms-up and base of skull to upper-thigh (limited Whole Body (LWB)), the injection site may not be routinely imaged. The purpose of this study was to evaluate the frequency of dose extravasations in FDG PET and the potential impact on SUV measurements. Methods: True Whole Body (TWB) FDG-PET/CT scans (including all extremities) of 400 patients were retrospectively reviewed. A log recorded cases of IV dose extravasations. When possible, SUVs were measured in two frequently used reference locations: mediastinum and liver. The SUVs were obtained in the same patients who had studies with and without FDG extravasations within an average of 3 months without interval therapy. Results: Of the 400 scans, 42 (10.5%) had extravasations on the maximum intensity projections (MIP) images. In scans with or without dose infiltration, FDG injection site was at or distal to the antecubital fossa in 97% of studies. Of those 42 cases, dose infiltration was within the LWB FOV in 29/42 (69%) and outside in the remaining 13/42 (31%). Of those 42 patients, 5 had repeat PET studies with no interval therapy. For those 5 patients, liver maximum SUV was 11.7% less in patients with infiltration than those without (2.22 ± 0.54 vs. 2.48 ± 0.6). Mediastinum SUVmax was 9.3% less in patients with infiltration than those without (1.72 ± 0.54 vs. 1.88 ± 0.49). Conclusion: We conclude dose extravasations were commonly encountered (10.5%) in PET/CT. However, it is underreported by at least 31% due to omitting injection site from the FOV. When present, extravasations may lead to underestimation of SUVmax. Therefore, it should not only be avoided but also reported in order to avoid false interpretations of the exam.